PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS PADA MATERI KEGIATAN EKONOMI - Novia Tantriyani; Kurniasari, Ria; Akbar, Aulia (Sebelas April Elementary Education, 2023)
The problem in this study is the low motivation and learning outcomes of students in social studies learning material on economic activities. To overcome these problems, researchers conducted research by applying the numbered head together (NHT) type of cooperative learning model. This study aims to determine the effect of the numbered head together (NHT) cooperative learning model on the motivation and learning outcomes of social studies in fourth grade students of SDN Mekarsari, Kasomalang District, Subang Regency. The research method used in this research is Classroom Action Research (CAR) by taking data face-to-face. This research was conducted on fourth grade students consisting of 10 students. The research was carried out in two cycles, where each cycle consisted of planning, action, observation and reflection. The initial condition of students' learning motivation was 43 (47.77%) or included in the very poor category. After applying the numbered head together (NHT) type cooperative model, it was found that there was an increase in students' motivation and learning outcomes on the material of economic activities. This can be seen from the increase in student learning motivation in the first cycle to get 59 (65.55%) or included in the sufficient category and in the second cycle there was an increase to 81 (90%) or included in the very good category. While on student learning outcomes, in the initial conditions only 2 (20%) students completed which, in the first cycle experienced an increase with 6 (60%) students completed while in the second cycle it increased to 9 (90%) who completed reaching the proportion of . Thus, it can be said that the application of the numbered head together (NHT) type cooperative model can increase motivation and learning outcomes in social studies learning economic activity materials in class IV SDN Mekarsari Kasomalang District, Subang Regency.